Прогностичке вредности азота урее/креатинина у крви и цистатина Ц код пацијената са радикалном нефректомијом због карцинома бубрежних ћелија - Wang, SiCheng; HaoLong,; Chao,; Jia, Bin (Journal of Medical Biochemistry, 2023)
Background: To evaluate the prognostic value of blood urea nitrogen/creatinine ratio (BUN/SCr) and cystatin C (Cys C) in patients with renal cell carcinoma (RCC) after radical nephrectomy.Methods: The study analyzed 348 patients with RCC who underwent radical nephrectomy. The optimal cutoff was obtained based on the ROC of specific survival outcomes and the maximum Youden index, and the patients were divided into four groups: Group 1 (low BUN/SCr-low Cys C), Group 2 (low BUN/SCr-high Cys C), Group 3 (high BUN/SCr-low Cys C) and Group 4 (high BUN/SCr-high Cys C). The primary endpoint was cancer-specific survival (CSS) and the secondary endpoint was disease-free survival (DFS).Results: A strong positive correlation was shown between BUN/SCr value and Cys C level. Patients with a higher BUN/SCr ratio (17.41) and Cys C level (3.98 mg/L) had poorer survival outcomes. Notably, patients in group 4 showed the worst CSS and DFS rates, while patients in groups 1 and 2 had better survival outcomes with no significant difference between the two groups. A higher BUN/SCr ratio (17.41) and high Cys C serum level (3.98 mg/L) were independent predictors of CSS and DFS, in addition to preoperative tumor size and pathological T (pT) stage.Conclusion: This study provides the first evidence of the independent prognostic importance of BUN/SCr ratio and Cys C in patients with RCC after radical nephrectomy.